Evidence for a cyclic diguanylic acid-dependent cellulose synthase in plants. - Amor, Y (1991)
Because numerous attempts to detect an activity for a cellulose synthase in plants have failed, we have taken a different approach toward detecting polypeptides involved in this process. The uniqueness of the structure and function of cyclic diguanylic acid (c-di-GMP) as an activator of the cellulose synthase of the bacterium Acetobacter xylinum makes it an attractive probe to use in a search for a c-di-GMP receptor that might be involved in the process in plants. Direct photolabeling with 32P-c-di-GMP has been used, therefore, to identify in plants two membrane polypeptides of 83 and 48 kD derived from cotton fibers that possess properties consistent with their being components of a c-di-GMP-dependent cellulose synthase. Based upon several criteria, the 48-kD species is proposed to be derived by proteolytic cleavage of the 83-kD polypeptide. Both polypeptides bind c-di-GMP with high affinity and specificity and show antigenic relatedness to the bacterial cellulose synthase, and the N-terminal sequence of the 48-kD polypeptide also indicates relatedness to the bacterial synthase. Ability to detect both cotton fiber polypeptides by photolabeling increases markedly in extracts derived from fibers entering the active phase of secondary wall cellulose synthesis. These results provide a basis for future work aimed at identifying and characterizing genes involved in cellulose synthesis in plants.